A novel structure for 4-channel all optical demultiplexer using 12-fold photonic quasicrystal - Pishvai Bazargani, Hamed (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
In this work, a new structure for a 4-channel all optical demultiplexer has been designed, using a 12-fold photonic quasicrystal (PQC). The structure used in this research is composed of air rods of 150 nm in diameter, arranged on silicon nitride substrate with a pitch of 260 nm and lattice constant of 0.25. The area of the structure is only 16 μm2 which is quite interesting for optical integrated circuit applications. The four channels are separated by introducing some defects to the crystal. Also, superprism effect in PQCs has been investigated by changing the tiling angle of input Gaussian modulated wave. Finally, four channels with spacing of 7.8 nm between channels one and two, 3.6 nm between channels two and three and 7.3 nm between channels three and four, around 0.6 μm as the central wavelength have been separated. The crosstalk level between adjacent channels is about –8 dB for channels one and two, –3 dB for channels two and three and –6.5 dB for channels three and four.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 661-668
Keywords: optyka; photonic quasicrystal; demultiplexer; defect; superprism effect